RNA, the epicenter of genetic information a new understanding of molecular biology - Mattick, John (Taylor and Francis, 2023)
"This book chronicles the muddled history of molecular biology. The complexity of animal and plant genomes and early conceptual triumphs further complicate this record. Key personalities, their hubris and prescient predictions are illustrated with quotes, archival material, photographs and diagrams to bring people, ideas and discoveries to life"--